2006
DOI: 10.1353/csd.2006.0061
|View full text |Cite
|
Sign up to set email alerts
|

The Convergent and Discriminant Validity of NSSE Scalelet Scores

Abstract: Faculty and administrators are more likely to take responsibility for student learning and development if they believe that assessment data represent their students and identify specific actions for improvement. An earlier study found that NSSE scalelets provide dependable metrics for assessing student engagement at the university, college, and department levels. Building on the earlier study, the findings of the current research indicate that the NSSE scalelets have greater explanatory power and provide riche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 21 publications
4
50
0
1
Order By: Relevance
“…Students' experiencing academic challenge (given opportunity to develop thinking, writing, application skills, etc) followed next as a contributor to students' growth and word of mouth recommendation. This confirms research findings of Pike (2006) that different types of student engagement have been found to be differently related to learning outcomes. For example, greater involvement with writing was positively related to gains in general education and in writing, and experience with information technology was positively related to gains in practical skills.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Students' experiencing academic challenge (given opportunity to develop thinking, writing, application skills, etc) followed next as a contributor to students' growth and word of mouth recommendation. This confirms research findings of Pike (2006) that different types of student engagement have been found to be differently related to learning outcomes. For example, greater involvement with writing was positively related to gains in general education and in writing, and experience with information technology was positively related to gains in practical skills.…”
Section: Discussionsupporting
confidence: 90%
“…Items were selected from the COS that measured students' time allocations and engagement in various activities reflecting benchmarks of effective educational practices, in addition to valued outcomes like students' growth, satisfaction, and their recommendation of the University. Such an approach of developing institutional scalelets was recommended by Pike (2006) for institutions not participating in NSSE but is using other instruments and who wanted to document impact on students' development and learning. Appendix provides list of COS items used to answer research questions.…”
Section: Procedures and Measurementioning
confidence: 99%
See 1 more Smart Citation
“…La validez y confiabilidad de la encuesta se ha demostrado en diversos estudios (National Survey of Student Engagement, 2012a; Kuh, Cruce, Shoup, Kinzie & Gonyea, 2008;Pike, 2006) e incluye una versión en español que ha sido empleada hasta el momento en México, Puerto Rico y España.…”
Section: Introductionunclassified
“…In commenting on the results of previous research employing NSSE data, Pike (2006) noted that use of a common method to measure the IVs and DVs can be problematic.…”
Section: Limitations Of This Researchmentioning
confidence: 99%